THU0448 Characterization of patients with chronic refractory gout who do and do not have clinically apparent tophi: response to pegloticase. (15th June 2017) - Edwards, NL; Singh, J; Troum, O; Yeo, A; Lipsky, P
Abstract : Background: The term "chronic refractory gout" defines a subset of chronic gout patients who are either intolerant of or unresponsive to standard uric acid (UA) lowering therapy (ULT). Subjects (N=85) meeting this definition were enrolled in a study of pegloticase (8 mg every 2 weeks [q2w], the approved dose), a mammalian recombinant uricase conjugated to polyethylene glycol that is approved for the treatment of gout refractory to conventional oral ULT. Of this group of subjects, 73% had clinically apparent tophi, whereas 27% did not. Objectives: To determine the clinical characteristics and response to pegloticase therapy in patients with chronic refractory gout with and without clinically apparent tophi. Methods: This analysis used results from two pivotal randomized controlled trials 1 to assess the clinical characteristics and the efficacy of pegloticase (8 mg q2w) in patients with chronic refractory gout with or without tophi at baseline. The results for serum urate (UA), flares, Patient Global Assessment (PGA), tender and swollen joints (TJC and SJC), bodily pain, Health Assessment Questionnaire-Disability Index (HAQ-DI), and the Arthritis-Specific Health Index (ASHI) and Bodily Pain from the Medical Outcomes Study Short Form 36 item (SF-36) were determined for each group. Results: The analysis included patients with chronic refractory gout, 62 with tophi at baseline and 23 without tophi. Chronic refractory gout patients in the two groups were similar at baseline, with the only significant differences in mean values between tophaceous and nontophaceous gout groups as follows: TJC, 14.2 vs 5.00 (P=0.01); SJC, 10.9 vs 3.4 (P=0.003); ASHI, 50.4 vs 64.7 (P=0.03); and HAQ-DI, 1.3 vs 0.6, respectively (P=0.001). Other measures of disease impact and comorbidities were not significantly different between groups. Treatment with pegloticase 8 mg q2w resulted in significant and comparable reductions in serum UA in both groups. Comparison of results from baseline and after 6 months of treatment for patients with tophi at baseline indicated significant reductions in serum UA (P<0.0001), flares (P<0.0001), PGA (P<0.0001), TJC and SJC (both P<0.0001), HAQ-DI (P=0.02), and SF-36 Bodily Pain (P<0.0001). Results for patients without clinically apparent tophi at baseline indicated significant improvements in serum UA (P<0.0001), flares (P=0.004), PGA (P=0.009), TJC (P=0.01), SJC (P=0.003), SF-36 Bodily Pain (P=0.03), and ASHI (P=0.0001). Conclusions: These results indicate that chronic refractory gout patients may present with or without clinically apparent tophi. Tophaceous patients are distinguished by more tender and swollen joints, greater disability, and greater arthritis severity, but otherwise are similar to nontophaceous patients. Both groups had significant clinical benefit over 6 months of treatment with pegloticase. References: Sundy JS, Baraf HS, Yood RA, et al. JAMA. 2011;306:711–720. Baraf HS, Becker MA, Gutierrez-Urena SR, et al. Arthritis Res Ther. 2013;15:R137. Disclosure of Interest: N. L. Edwards Consultant for: AstraZeneca, Horizon Pharma, Ironwood Pharmaceuticals, SOBI International, J. Singh: None declared, O. Troum Shareholder of: Theralogix, Grant/research support from: Abbvie, Amgen, CORONA, Novartis, Pfizer, R-Pharm, Consultant for: Abbvie, Amgen, BMS, Pfizer, Roche, Genentech, Speakers bureau: Abbvie, Amgen, BMS, Celgene, Novartis, Pfizer, Roche, Genentech, A. Yeo Consultant for: Horizon Pharma, P. Lipsky Consultant for: AstraZeneca, Celgene, EMD Serono, GSK, Horizon Pharma, Janssen, Medimmune, Pfizer, Roche, Sanofi, UCB